Flexible self-supporting film electrode based on titanium-oxygen cluster and metal ion complex modified MXene and preparation method of flexible self-supporting film electrode
By modifying the MXene nanosheets to form stable titanium oxygen clusters and metal ion complex MOF types, the problems of reduced electrochemical performance and insufficient mechanical flexibility caused by MXene nanosheet stacking are solved, and higher electrochemical performance and mechanical flexibility are achieved.
Patent Information
- Application Number
- CN202510043872.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-10
AI Technical Summary
MXene nanosheets are easy to stack, resulting in longer ion conduction paths, reducing their electrochemical properties, and also improving their mechanical flexibility.
By modifying with titanium oxide clusters and metal ion complexes, a stable MOF type is formed, which alleviates the problem of MXene nanosheet stacking and improves electrochemical activity. The titanium oxygen cluster is a cage-shaped cluster that stretches the distance between MXene nanosheets, forms a three-dimensional network structure and enhances mechanical flexibility.
The electrochemical performance and mechanical flexibility of MXene electrodes have been improved, enhancing its application potential in flexible wearable electronics.
Smart Images

Figure CN119786272A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage devices, and in particular to a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene and a preparation method thereof. Background Art
[0002] As the practicality of flexible electronic products has been increasingly valued, flexible supercapacitors have emerged to meet the energy storage needs of these products. They not only have excellent flexibility, but also can achieve fast charging and discharging, and have stable cycle performance. Compared with traditional solid-state batteries, they are more suitable for daily applications. Flexible electrodes are the core components of flexible supercapacitors and have a significant impact on the performance of wearable and implantable electronic devices. New materials such as carbon nanotubes and graphene are usually used to achieve higher energy storage capacity and faster charging and discharging speeds.
[0003] MXene, a new type of two-dimensional material composed of transition metal carbides, nitrides or carbonitrides, has shown broad application prospects in the field of energy storage due to its excellent film-forming properties, electrical conductivity, adjustable surface functional groups and charge storage method with pseudocapacitive characteristics. However, MXene nanosheets often stack, which makes the ion conduction path longer and reduces its electrochemical performance. In addition, the mechanical flexibility of MXene nanosheets needs to be improved.
[0004] Therefore, a new MXene processing method is urgently needed to prepare a more stable and higher-performance MXene electrode to meet the needs of scientific and technological development. Summary of the invention
[0005] Based on this, the present invention has developed a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene, which has good mechanical flexibility and electrochemical properties. The present invention provides a type of MOF that can stably combine with MXene under acidic conditions, alleviating the problem of restacking of two-dimensional MXene nanosheets, while also providing more active sites to improve its electrochemical activity.
[0006] An object of the present invention is to provide a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, wherein the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution;
[0007] in,
[0008] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and metal ion dispersion;
[0009] In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets;
[0010] The titanium oxide clusters are cage-like clusters.
[0011] Furthermore, the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes has a multilayer structure with an interlayer spacing ranging from 5.91 to 6.33 μm.
[0012] Furthermore, in the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, the doping percentage of MXene nanosheet clusters is 10%-40%.
[0013] Another object of the present invention is to provide a method for preparing the above-mentioned flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene, comprising the following steps:
[0014] S1. Put the MAX raw material into acid solution for etching, wash it to neutrality, and then use intercalation agent for intercalation, and separate to obtain MXene colloidal solution;
[0015] S2, mixing Ti(OiPr)4, benzoic acid, metal ion dispersion and solvent, and reacting to obtain a titanium oxide cluster precursor dispersion;
[0016] S3, blending the MXene colloid solution and the titanium oxide cluster precursor dispersion, and performing a hydrothermal reaction under an inert atmosphere, purifying, washing, and drying to obtain MXene nanosheet clusters;
[0017] S4. The MXene nanosheet clusters are doped into the MXene colloidal solution by stirring, and then purified and dried to obtain the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes.
[0018] Further, the chemical formula of the MAX raw material is MAX;
[0019] in,
[0020] The M is selected from at least one of Ti, V, Nb, Mo, Zr, Cr or Hf;
[0021] A is selected from at least one of Al, Ga, Si, Ti, Sn or Ge;
[0022] The X is selected from at least one of C and N.
[0023] Furthermore, the acid solution is a mixed solution of HCl and HF.
[0024] Furthermore, the intercalation agent is lithium chloride.
[0025] Furthermore, in the titanium oxide cluster precursor dispersion, the structural formula of the titanium oxide cluster precursor is Ti8M2BA 16 , forming a cage-like cluster;
[0026] in,
[0027] The M is a metal ion;
[0028] The BA is a benzoate ligand.
[0029] Furthermore, the metal ions are selected from one or more of lanthanide, actinide or transition metals.
[0030] Furthermore, in step S3, the solute mass ratio of the MXene colloid solution to the metal ion dispersion is 1:0.5-1:5.
[0031] Further, in step S4, the mass ratio of the MXene colloid solution to the MXene nanosheet clusters is 1:0.1-1:0.65;
[0032] The concentration of the MXene colloid solution is 3-30 mg·mL -1 .
[0033] Furthermore, the hydrothermal reaction temperature is 80-150° C., and the insulation time is 48-72 hours.
[0034] Another object of the present invention is to provide the application of the above-mentioned flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene in energy storage devices.
[0035] The present invention has the following beneficial effects:
[0036] The present invention provides a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes. The titanium oxide clusters and metal ions form a type of MOF that can stably bind to MXene under acidic conditions, which alleviates the problem of restacking of two-dimensional MXene nanosheets and also provides more active sites to improve its electrochemical activity. On the one hand, the titanium oxide clusters are cage-like clusters, which open up the distance between MXene nanosheets, expand the interlayer spacing, facilitate the transport of ions, and improve the electrochemical performance. On the other hand, the MXene sheets are connected by the clusters to form a three-dimensional network structure. When subjected to external forces, the MXene sheets interact with each other to reduce stress concentration, thereby improving the mechanical flexibility of the thin film electrode and promoting the application of flexible thin film electrodes in flexible wearable electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The electrochemical performance test diagram of the thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 in a Swagelok battery is shown;
[0038] in,
[0039] Figure 1 (a) shows the -1 CV curves of Examples 1-4 and Comparative Examples 1-3 at scanning rates;
[0040] Figure 1 (b) shows the -1 GCD curves of Examples 1-4 and Comparative Examples 1-3 at scanning rates.
[0041] Figure 2 The macroscopic photographs of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 in a bent state, a folded state, after filtration and drying, and under vertical load are shown;
[0042] in,
[0043] Figure 2 (a) shows a macroscopic photograph in a bent state;
[0044] Figure 2 (b) shows a macroscopic photograph of the folded state;
[0045] Figure 2 (c) shows a macroscopic photograph after filtration and drying;
[0046] Figure 2 (d) shows a macroscopic photograph under vertical load.
[0047] Figure 3The XRD comparison diagram of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and the MXene thin film electrode prepared in Comparative Example 3 is shown;
[0048] in,
[0049] Figure 3 (a) shows the XRD pattern of the MXene thin film electrode prepared in Comparative Example 3;
[0050] Figure 3 (b) shows the XRD pattern of the flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes prepared in Example 2.
[0051] Figure 4 Scanning electron microscope (SEM) images of a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and a MXene thin film electrode prepared in Comparative Example 3 are shown;
[0052] in,
[0053] Figure 4 (a) shows a cross-sectional view of MXene;
[0054] Figure 4 (b) shows the MXene surface image;
[0055] Figure 4 (c) shows the cross-sectional view of the MXene / Ti-O-La cluster;
[0056] Figure 4 (d) shows the surface image of MXene / Ti-O-La cluster. DETAILED DESCRIPTION
[0057] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0058] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0059] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that vary depending on the desired properties to be obtained by the present invention.
[0060] The filter membrane in the embodiment of the present invention is a cellulose water filter membrane with a pore size of 0.45 μm, purchased from Shanghai Xingya Purification Material Factory
[0061] The water used in the embodiments of the present invention is deionized water.
[0062] Example 1
[0063] A flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, which is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution;
[0064] in,
[0065] The titanium oxide cluster precursor dispersion is obtained by a mixed reaction of Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;
[0066] In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets;
[0067] The titanium oxide clusters are cage-like clusters.
[0068] The method for preparing the above-mentioned flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene comprises the following steps:
[0069] S1. At room temperature, measure 1ml HF, 2ml H2O, and 7ml HCl and pour them into a polytetrafluoroethylene reaction bottle, stir for 5min to mix evenly. Weigh 0.5g of Ti3AlC2 MAX phase with excess Al (the molar ratio of each element in the MAX phase is Ti:C:Al=2:1.25:2.2, here the Ti3AlC2 MAX phase with excess Al is called Al-Ti3AlC2, the same below) and add it to the mixed solution, stir in a water bath at 40°C for 36h, rotate at 400r / min, etch, and repeatedly centrifuge and wash the obtained etched product until neutral, and remove the lower layer after centrifugation to precipitate as multilayer MXene. Weigh 0.5g of LiCl, stir and dissolve in 25ml water to make a LiCl solution, transfer the multilayer MXene to the LiCl solution, and stir magnetically for 24h at a speed of 400r / min. Then transfer to a centrifuge tube, centrifuge and wash until the upper dispersion turns black and the lower precipitate expands, ultrasonicate for 30 minutes, centrifuge at 1500r / min for 20 minutes, take the upper dispersion, and then centrifuge at 3500r / min for 15 minutes, take the upper dispersion to obtain a MXene colloidal solution. Take 2ml of the MXene colloidal solution, vacuum filter, dry, and peel off the film to determine the concentration of the colloidal solution (usually, the concentration of the MXene colloidal solution prepared by 0.5g of Al-Ti3AlC2 is about 10mg / ml);
[0070] S2, prepare a 10 mg / ml lanthanum chloride aqueous solution with deionized water, dissolve 0.61 ml of Ti(OiPr)4, 1.22 g of benzoic acid and 8 ml of the lanthanum chloride aqueous solution in 6 ml of acetonitrile, and ultrasonicate for 0.5 h to form a titanium oxide cluster precursor dispersion;
[0071] S3, blending the titanium oxide cluster precursor dispersion with 20 mg of MXene colloidal solution, stirring to make the mixture uniform, and then performing a hydrothermal reaction under nitrogen protection, keeping the reaction at 100° C. for 72 hours, naturally cooling to room temperature, centrifuging at 3500 r / min for 5 minutes to wash multiple times to remove acetonitrile, and then drying to obtain powdered MXene nanosheet clusters loaded with titanium oxide clusters and lanthanum metal ion complexes;
[0072] S4. Dissolve 50 mg of the MXene nanosheet clusters in 10 ml of water to prepare a 5 mg / ml Ti-O-La cluster dispersion. Take 1 ml of the Ti-O-La cluster dispersion, mix and stir it with 20 mg of MXene colloidal solution, and then vacuum filter it with a 0.45 μm cellulose water filter membrane. Vacuum dry it at room temperature for 4 hours to obtain a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes.
[0073] Example 2
[0074] A flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, which is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution;
[0075] in,
[0076] The titanium oxide cluster precursor dispersion is obtained by a mixed reaction of Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;
[0077] In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets;
[0078] The titanium oxide clusters are cage-like clusters.
[0079] The preparation method of this embodiment is different from that of Example 1 in that, in step S4, 60 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 6 mg / ml Ti-O-La cluster dispersion, and the rest of the preparation method is the same as that of Example 1.
[0080] Example 3
[0081] A flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, which is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution;
[0082] in,
[0083] The titanium oxide cluster precursor dispersion is obtained by a mixed reaction of Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;
[0084] In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets;
[0085] The titanium oxide clusters are cage-like clusters.
[0086] The preparation method of this embodiment is different from that of Example 1 in that, in step S4, 70 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 7 mg / ml Ti-O-La cluster dispersion, and the rest of the preparation method is the same as that of Example 1.
[0087] Example 4
[0088] A flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, which is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution;
[0089] in,
[0090] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and cerium chloride aqueous solution;
[0091] In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets;
[0092] The titanium oxide clusters are cage-like clusters.
[0093] The preparation method of this embodiment is different from that of Example 1 in that, in step S2, the lanthanum chloride aqueous solution is replaced with a cerium chloride aqueous solution of the same concentration; in step S4, 60 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 6 mg / ml Ti-O-Ce cluster dispersion, and the rest of the preparation method is the same as that of Example 1.
[0094] Comparative Example 1
[0095] A MXene thin film electrode is prepared from a MXene colloidal solution. The preparation method thereof comprises the following steps:
[0096] S1. Prepare a MXene colloidal solution, the preparation method of which is the same as that of Example 1;
[0097] S2. Take 2 ml of the MXene colloid solution, vacuum filter it with a filter membrane, and vacuum dry it at room temperature for 4 hours to obtain the MXene thin film electrode.
[0098] Comparative Example 2
[0099] A MXene thin film electrode is prepared by hydrothermal reaction of a MXene colloidal solution. The preparation method comprises the following steps:
[0100] S1. Prepare a MXene colloidal solution, the preparation method of which is the same as that of Example 1;
[0101] S2. The MXene colloidal solution is subjected to a hydrothermal reaction under nitrogen protection. After the reaction is kept at 100° C. in a vacuum oven for 72 hours, it is naturally cooled to room temperature. The obtained product is vacuum filtered with a filter membrane and vacuum dried at room temperature for 4 hours to obtain the MXene thin film electrode.
[0102] Comparative Example 3
[0103] A MXene thin film electrode is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution.
[0104] The difference between the preparation method of the MXene thin film electrode and that of Example 1 is that in step S2, no lanthanum chloride aqueous solution is added, and the rest of the preparation method is the same as that of Example 1.
[0105] Test Case
[0106] The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were tested, and the test methods adopted were all conventional test methods used by those skilled in the art unless otherwise specified.
[0107] Test method:
[0108] (1) The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to electrochemical performance tests in a Swagelok cell.
[0109] (2) The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were directly used as working electrodes, activated carbon was used as counter electrode, and Ag / AgCl was used as reference electrode to construct a three-electrode system. (a) Cv and (b) GCD tests were performed in 3M H2SO4 electrolyte. -1 and 1A·g -1 Test the specific capacitance.
[0110] Test results such as Figure 1 And as shown in Table 1.
[0111] Figure 1 The electrochemical performance test diagram of the thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 in a Swagelok battery is shown;
[0112] in,
[0113] Figure 1 (a) shows the -1 CV curves of Examples 1-4 and Comparative Examples 1-3 at scanning rates;
[0114] Figure 1 (b) shows the -1 GCD curves of Examples 1-4 and Comparative Examples 1-3 at scanning rates.
[0115] Table 1 Specific capacitance test results
[0116]
[0117]
[0118] Depend on Figure 1 As shown in Table 1, compared with Comparative Example 1, the electrochemical performance of Comparative Example 2 is improved after hydrothermal treatment. Compared with Comparative Example 2, the electrochemical performance of the thin film electrode of Comparative Example 3 is further improved by loading titanium oxide clusters. As shown in Examples 1-4, after the metal ions coordinate the titanium oxide clusters to form a three-dimensional network structure, the electrochemical performance of the thin film electrode is greatly improved. Among them, the electrochemical performance of the thin film electrode corresponding to Example 2 treated with 6 mg / ml lanthanum ion dispersion is the best, and the specific capacitance measured in 3M H2SO4 electrolyte reaches 660F·g -1 .
[0119] Figure 2 The macroscopic photographs of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 in a bent state, a folded state, after filtration and drying, and under vertical load are shown;
[0120] in,
[0121] Figure 2 (a) shows a macroscopic photograph in a bent state;
[0122] Figure 2 (b) shows a macroscopic photograph of the folded state;
[0123] Figure 2 (c) shows a macroscopic photograph after filtration and drying;
[0124] Figure 2 (d) shows a macroscopic photograph under vertical load.
[0125] Depend on Figure 2 It can be seen that the composite thin film electrode can be obtained by vacuum filtration, can be rolled up and bent without breaking, has a certain load capacity, and exhibits excellent mechanical flexibility.
[0126] Figure 3 The XRD comparison diagram of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and the MXene thin film electrode prepared in Comparative Example 3 is shown;
[0127] in,
[0128] Figure 3 (a) shows the XRD pattern of the MXene thin film electrode prepared in Comparative Example 3;
[0129] Figure 3 (b) shows the XRD pattern of the flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes prepared in Example 2.
[0130] Depend on Figure 3 It can be seen that Figure 3 In (b), different Figure 3 The peaks of (a) were analyzed and compared, indicating that a MXene film loaded with titanium oxide clusters and lanthanum metal ion complexes was successfully synthesized.
[0131] Figure 4 Scanning electron microscope (SEM) images of a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and a MXene thin film electrode prepared in Comparative Example 3 are shown;
[0132] in,
[0133] Figure 4 (a) shows a cross-sectional view of MXene;
[0134] Figure 4 (b) shows the MXene surface image;
[0135] Figure 4 (c) shows the cross-sectional view of the MXene / Ti-O-La cluster;
[0136] Figure 4 (d) shows the surface image of MXene / Ti-O-La cluster.
[0137] Figure 4 The SEM cross-sectional image shows that the MOF structure formed by titanium oxide clusters and lanthanum metal ion complexes is effectively inserted into the interlayer of MXene nanosheets, which expands the interlayer spacing and facilitates the transport of ions. The SEM surface image clearly shows that the MXene nanosheets have adsorbed a large amount of titanium oxide clusters and lanthanum metal ion complex particles, which effectively improves the electrochemical performance of the thin film electrode.
[0138] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0139] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, characterized in that: The flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into a MXene colloidal solution; in, The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and metal ion dispersion; In the MXene nanosheet clusters, titanium oxide clusters are in-situ grown on the MXene nanosheets; The titanium oxide clusters are cage-shaped clusters.
2. The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 1, characterized in that: The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes has a multilayer structure with an interlayer spacing ranging from 5.91 to 6.33 μm.
3. The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 1, characterized in that: In the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes to modify MXene, the doping percentage of the MXene nanosheet clusters is 10%-40%.
4. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to any one of claims 1 to 3, characterized in that: The steps include: S1. Put the MAX raw material into acid solution for etching, wash it to neutrality, and then use intercalation agent for intercalation, and separate to obtain MXene colloidal solution; S2, mixing Ti(OiPr)4, benzoic acid, metal ion dispersion and solvent, and reacting to obtain a titanium oxide cluster precursor dispersion; S3, blending the MXene colloid solution and the titanium oxide cluster precursor dispersion, and performing a hydrothermal reaction under an inert atmosphere, purifying, washing, and drying to obtain MXene nanosheet clusters; S4. The MXene nanosheet clusters are doped into the MXene colloidal solution by stirring, and then purified and dried to obtain the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes.
5. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 4, characterized in that: The chemical formula of the MAX raw material is MAX; in, The M is selected from at least one of Ti, V, Nb, Mo, Zr, Cr or Hf; The A is selected from at least one of Al, Ga, Si, Ti, Sn or Ge; The X is selected from at least one of C and N.
6. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 4, characterized in that: In the titanium oxide cluster precursor dispersion, the structural formula of the titanium oxide cluster precursor is Ti8M2BA 16 ; in, The M is a metal ion; The BA is a benzoate ligand.
7. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 6, characterized in that: The metal ions are selected from one or more of lanthanide, actinide or transition metals.
8. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 4, characterized in that: In step S4, the mass ratio of the MXene colloid solution to the MXene nanosheet clusters is 1:0.1-1:0.65; The concentration of the MXene colloid solution is 3-30 mg·mL -1 .
9. The method for preparing a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 4, characterized in that: The hydrothermal reaction temperature is 80-150° C., and the insulation time is 48-72 hours.
10. Use of the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes as described in any one of claims 1 to 3 in energy storage devices.
Citation Information
Patent Citations
MXene loaded noble metal cluster catalyst as well as preparation method and application thereof
CN113235108A
Method for preparing titanium-based metal organic framework membrane from titanium oxide clusters
CN115245764A
Flexible film electrode based on plant polyphenol and metal ion complex modified MXene and preparation method thereof
CN117936280A
Preparation method of flexible self-supporting MXene / graphene / carbon nanotube film electrode material
CN118213206A
Cited By
Preparation method and application of flexible self-supporting film electrode based on titanium-oxygen cluster and hydroximic acid complex modified MXene
CN122067921A